Erosion resistance behavior of recycled plastic concrete in sodium sulfate solution. (21st March 2022) - Wu, Haikuan; Miao, Yichen; Zhu, Haowei; Zhao, Chao; Shu, Zhile; Liu, Changwu
Highlights: With the increase of erosion time and concentration, the changes law of apparent morphology, relative mass and ultrasonic wave velocity of RPC were revealed. The variation law of compressive strength of RPC under different concentration erosion was revealed. The variation law of compressive strength with the change of relative mass and ultrasonic wave velocity was revealed. The erosion deterioration mechanism of RPC was revealed. Abstract: With the development of economy, the global waste plastics are gradually increasing. Adding recycled particles of waste plastics to concrete materials can effectively recover waste plastics, but it will also have an impact on the sodium sulfate resistanceperformance of concrete.In this work, at the macro level, the three concentrations (3%, 5%, and 7%)sodium sulfate resistance of recycled plastic concrete (RPC)andnormalconcrete (NC) were analyzed and evaluated from its appearance, relative mass, compressive strength, andultrasonic wave velocity. From the microscopic aspect, the microstructure and phase composition at 5% erosion concentration were tested and analyzed by SEM, XRD, and FT-IR.The deterioration mechanism of RPC eroded by sodium sulfate solution was analyzed.Results showed thatthe effect of sodium sulfate solution on RPC is similar to that of NC in the early stage. In the later stage of erosion, the erosion degree of RPC is less than that of NC. The deterioration characteristics of RPCwere mainly the development process of corners, edges, and then surface, and the rate of mass increase and ultrasonic wave velocity decrease gradually increasedwith the increase of erosion concentration and erosion time.Under 3% and 5% concentration erosion, the variation range of compressive strength was lower than that of normal concrete in the whole erosion stage, and under 7%concentration erosion, it showed the opposite effects.The compressive strength increased first and then decreased with the increase of mass change rate and the decrease of ultrasonic wave velocity.Taking the compressive strength as the damage parameter, the damage degree model of recycled plastic concrete eroded by sodium sulfate solution was deduced.The erosion deterioration mechanism of RPC was revealed by microstructure and phase analysis.